Tourist Product Designed For The Commercialization Of Strawberry-Based Beverages - Beltrán Martínez, Elsy Margarita; Grande García, Yoselyn Iveth; Rivera Henríquez, Margarita Guadalupe (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2025)
Disponible en soporte impreso